IMPROVING STUDENTS’ READING COMPREHENSION BY USING REDW (READ, EXAMINE, DECIDE, AND WRITE ) STRATEGY TO THE TENTH GRADE STUDENTS OF MA AL-MUAWWANAH GUNUNG MEGANG MUARA ENIM SUMATERA SELATAN - Susiana Susiana (Edukasi, 2016)
This research aimed to find out whether or not the using of REDW (Read, Examine, Decide,and Write) strategy significantly improves the students reading comprehension to the tenth grade students of MA Al-Muawwanah Gunung MegangMuaraEnim. To explain the improvement, the researcher used a quasi experimental method involved an experimental group and control group both was given pre-test and post-test which consisted of 31 students. The test was given to get the data with 30 questions in the form of multiple choice and open questions and to analyze them usingSPSS 20.0.From the result analysis of significant improvement on students’ reading comprehension achievement taught using REDW strategy, it was found that the p-output in experimental group was 0.000 with df=30 and t-value 5.936. It could be interpreted that there was a mean significant improvement on students’ reading comprehension score taught using REDW since the p-output was lower than 0.05 and t-value was higher than t-table (2.04).